Laboratory tests in geriatric patients - an overview of the latest reports - Monika Prylińska; Paula Piątkowska; Mateusz Porada; Natalia Skierkowska; Karolina Kubiak; Dorota Szewczak; Marta Bryfczyńska; Joanna Osiak; Paulina Trawka; Paulina Kiszewska; Adrianna Nieciecka; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Laboratory tests are extremely important in patient's monitoring and/or diagnosing. We described those that are particularly significant for elderly patients, namely: peripheral blood morphology, arterial blood gasometry, cancer markers. The aim of this article is to summarize current knowledge about laboratory tests important in geriatrics, as well as draw attention to the diverse use of laboratory tests in clinical practise.